1994
DOI: 10.1038/ki.1994.222
|View full text |Cite
|
Sign up to set email alerts
|

Tubular catabolism of albumin is associated with the release of an inflammatory lipid

Abstract: Proteinuria and tubulointerstitial inflammation (TII) correlate with progression to renal failure in human glomerulonephritis. Various forms of experimental nephrotic syndrome are associated with TII. To study the genesis of TII, we utilized the model of albumin overload. Rats received intraperitoneal bovine serum albumin (BSA) for 1 to 14 days, developing heavy proteinuria. A predominantly macrophage interstitial infiltrate was present at days 3, 7 and 14. The urine of the rats contained a factor chemotactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 29 publications
0
69
0
Order By: Relevance
“…Studies using these models have suggested that the proteinuria itself could induce the progressive interstitial injury, and several hypotheses have been proposed as potential mechanisms of proteinuria-induced tubulointerstitial injury. These include direct tubulotoxicity of high protein concentrations (18) or that specific proteins such as growth factors, lipoproteins (19,20), transferrin (21), or activated complement components (22, 23) may be damaging. Recent studies have emphasized the role of the MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using these models have suggested that the proteinuria itself could induce the progressive interstitial injury, and several hypotheses have been proposed as potential mechanisms of proteinuria-induced tubulointerstitial injury. These include direct tubulotoxicity of high protein concentrations (18) or that specific proteins such as growth factors, lipoproteins (19,20), transferrin (21), or activated complement components (22, 23) may be damaging. Recent studies have emphasized the role of the MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that are bound to albumin, such as free fatty acids (FFA), instead have been implicated to be causative in proinflammatory activation or injury of cultured proximal tubular cells (33). Kees-Folts et al (34), by studying the specific response of cultured tubular cells to albumin-bound molecules, found that the tubular metabolism of albumin-bound fatty acids could generate macrophage chemotactic activity, whereas delipidated albumin produced little such activity. It was suggested that fatty acids can be released during degradation of albumin, HDL, or LDL.…”
Section: Glomerular Proteinuria As Signal For Interstitial Inflammatimentioning
confidence: 99%
“…This lipid accumulation results in considerable metabolic perturbation (18). Proximal tubular segments exposed to FA-bearing albumin but not FA-free albumin elaborate a lipid chemoattractant that has a potentially key role in the induction of interstitial inflammation (19).…”
Section: Njb18@leacukmentioning
confidence: 99%